How is med-arb regulated in Hong Kong? - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2013)
In this post on the Kluwer Mediation Blog, the Arbitration Ordinance (AO) and the Mediation Ordinance (MO) to the multi-tiered dispute resolution (MDR) practice in Hong Kong are analysed.